Viewpoints on "Three assessments of Finland's economic crisis and economic policy" - Jarmo Kontulainen; Jouko Vilmunen (Bank of Finland, 1994)
This paper summarizes the basic arguments given by professors Christian Bordes, David Currie and Hans Söderström in their reports on the state and behaviour of the Finnish economy prior to mid 1993. The focus is primarily on the analytical frameworks or models used by the professors to organize their thoughts on the Finnish economy, and, admittedly, at some risk of over-simplification interpretes the reports through common analytical principles. The paper argues that basically each of the reports subscribes to the idea of a credit cycle as the driving force behind the development of the Finnish economy during the last ten years or so. Thus the very nature of the credit cycle is analyzed in the paper and interpreted in a way suitable for economic policy analysis. This discussion is followed by the policy analysis, which is organized through a sequence of policy issues and proposals raised by the professors in their reports. The paper tries to emphasize and evaluate those aspects of the analysis pursued by the professors which relate to the (lack of) credibility of the then prevailing policy regime and the feasibility of the various policy measures taken. Finally, the paper draws attention to some of the ideas discussed by the professors related to future policy options in Finland.
URN:NBN:fi:bof-201501291033
Keywords: 330